Analysis of patient preferences on patient-provider interactions through the OpenNotes online portal in dermatology - Christopher Henderson, MD, MPhil; Zachary P. Nahmias, MD; Alan Fossa, MPH; Ethan Barnes, BA; Susan Huang, MD (Wolters Kluwer, 2021)
Background: Many medical centers are beginning to use OpenNotes (ON) to empower patients. However, there is a lack of literature reviewing the ON system in dermatology and any differences in attitudes between men and women. If so, it is uncertain what concerns are more important to female patients. Given the complex lexicon of notes in dermatology, the outpatient setting of dermatology practices, and the often-complex nature of treatment regimens, investigation was merited.Objective: This paper aimed to evaluate a survey of dermatologic patients on their attitudes toward the ON system.Methods: From July through October 2015, 333 dermatologic patients at the Beth Israel Deaconess Medical Center completed an anonymous, voluntary, 25-question survey of the ON system while in the waiting room. Approximately 60% of respondents were female and 40% were male. Respondents were older, with 27% age >65 years, 21% between 56 and 65 years, 16% between 46 and 55 years, 17% between 36 and 45 years, 14% between 26 and 35 years, and 4% between 18 and 25 years. Eighty-five percent of respondents were white, and 73% had, at minimum, graduated from college.Results: Patient response to ON was positive, with 93% agreeing ON is a good idea. Of the patients who accessed their own notes (69% of respondents), 99.6% desired continued access. In addition, 85.6% of patients felt ON allowed them to control their own health, and 70% reported increased confidence in their dermatologist. Nineteen percent of respondents thought ON presented a privacy concern.Conclusion: The results showed that female patients strongly desire access to their medical records, but concerns about privacy and security exist. Preliminary analysis by a statistician did not find any statistically significant variations between men and women within the results of the survey. Due to the wide agreement in responses, it is unlikely that there are significant differences in opinion on ON between men and women.